Pengembangan Media Pembelajaran berbasis IT pada Guru di tingkat Sekolah Dasar - Setyawan, Dedi; arumsari, andini dwi (Universitas Narotama, 2023)
One of the educational processes is carried out by using media as a means to support and facilitate the teaching and learning process at primary level schools so that it can be carried out optimally and sustainably. In teaching and learning activities using IT-based learning media can make students motivated in their learning so that they are expected to be able to provide subject material that students find difficult to understand can be simplified by using media assistance, especially audiovisual media. The aim of this research is to determine the effectiveness of IT-based learning media for teachers at the elementary school level. Data were collected using a pre-test and post-test given to elementary school teachers before and after the teaching and learning process using IT. The subjects in this research were 19 elementary school teachers in Surabaya. Data analysis was carried out using the t-test with a result of 0.00 which means it is significant. The conclusion in this research is that IT-based learning media is effectively used for students at elementary school level